The Resonant Brain (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This Special Issue is dedicated to Stephen Grossberg, Professor Emeritus at the Department of Biomedical Engineering of Boston University (BU), Wang Professor of Cognitive and Neural Systems, and a former Director of the Center for Adaptive Systems of BU. Grossberg is an internationally acclaimed scientist and a pioneer in fundamental principles, mechanisms, and model architectures that form the foundation of contemporary neural network research. Articles in this collection focus on the perceptual integration of sensory information, cognitive representation, and mechanisms feeding consciousness.